Response of Boron and Light on Morph-Physiology and Pod Yield of Two Peanut Varieties - Md. Quamruzzaman; Md. Jafar Ullah; Md. Fazlul Karim; Nazrul Islam; Md. Jahedur Rahman; Md. Dulal Sarkar (International Journal of Agronomy)
Boron is an important micronutrient that enhances vegetative growth and yield of crops, like peanut. Light also plays an important role in pegging of peanut. There has been little information regarding the application of boron and light in peanut in Bangladesh. Therefore, a field experiment was conducted to study the response of boron and light on morph-physiology and pod yield of two peanut varieties. Treatments considered two peanut varieties, namely, Dhaka-1 and BARI Chinabadam-8, three levels of boron (B), namely, 0-kg B ha−1 (B0), 1-kg B ha−1 (B1), and 2-kg B ha−1 (B2), and two levels of light, namely, normal day light (≈12 h light) and normal day light + 6 h extended red light at night (≈18 h light). Result revealed that days to first-last emergence and days to first-50% flowering took shorter times and vegetative growth, pods dry weight plant−1, pod yield, and germination were markedly increased with the application of boron. Vegetative growth and germinations were significantly increased in light, but the lowest leaf area, pods dry weight plant−1, and pod yield were found in light. Without germination, the highest vegetative growth, reproductive unit, and pod yield were observed from BARI Chinabadam-8. Days to first-last emergence, days to first-50% flowering, and number of branches plant−1 were found linearly related to pod yield.